Saccharomyces cerevisiae osteomyelitis in an immunocompetent baker. (2016) - Seng, Piseth; Cerlier, Alexandre; Cassagne, Carole; Coulange, Mathieu; Legré, Regis; Stein, Andreas
Abstract: Invasive infection caused by Saccharomyces cerevisiae is rare. We report the first case of osteomyelitis caused by S. cerevisiae (baker's yeast) in a post-traumatic patient. The clinical outcome was favorable after surgical debridement, prolonged antifungal treatment and hyperbaric oxygen therapy.